Features of the management of reproductive aged women with adenomyosis in the post-COVID period - A.V. Bulhar; M.B. Zaporozhchenko (Publishing House TRILIST, 2023)
Objectives: development of an algorithm for managing women of reproductive age with adenomyosis of I-IV degrees of severity after COVID-19 by studying anamnestic, clinical, laboratory indicators, results of instrumental and hardware research and determining personalized therapy and prevention. Materials and methods. We monitored 120 reproductive aged women with adenomyosis after COVID-19, who were divided into group B (60 women with adenomyosis of the I-II degree of severity) and group C (60 women with adenomyosis of the III-IV degree of severity). Groups B and C were divided into 2 subgroups: subgroups B1 and C1 received the proposed therapy; subgroups B2 and C2 received standard therapy. All women underwent a clinical and laboratory examination, which included the study of the general condition, clinical and biochemical parameters, examination of biological fluids (blood, urine, vaginal contents), histomorphological study of the tissues of uterus, ovaries, hardware and instrumental methods of examination. The results were evaluated before treatment, after 3, 6 and 12 months of therapy, comparing between groups B and C. Results. The effectiveness of the proposed algorithm is confirmed by a significant difference (p < 0.05) in the reduction of the frequency of complaints, symptoms of exacerbation of extragenital and gynecological pathology, stabilization of indicators of general blood test, functional liver tests, lipid and cholesterol metabolism, reduction of indicators of hypercoagulation, activity of biological markers of inflammatory processes, increase the vitamin D and magnesium values, positive changes in the vaginal biocenosis, a decrease in the frequency of herpes simplex virus types 1 and 2 detection, an increase in the number of Lactobacillus sp., positive dynamics of uterine ultrasound parameters, including the state of blood flow in a. uterus in the observation dynamics after 3, 6 and 12 months. Conclusions. Women of reproductive age with adenomyosis of various degrees of severity after suffering from the COVID-19 disease are subject to personalized dispensary supervision, which includes diagnostic, therapeutic, preventive measures in the dynamics of observation. The definition of the measures of such algorithm should be based on the results of proven pathological changes in the body, namely: exacerbation of extragenital diseases, combined gynecological pathology, blood hypercoagulation and microcirculation disorders, activity of biological markers of inflammation, levels of sex hormones, vitamin D, magnesium, state of vaginal biocenosis.